(untitled) (International journal of artificial intelligence, 2025)
The article discusses the results of field research conducted on the territory of Olmaliq for engineering and seismological justification of the master plan for the development of the city. Geophysical and engineering-geological surveys were carried out to assess the influence of soil conditions on seismic intensity parameters. Calculated values of peak ground accelerations on a free surface were obtained using the STRATA program. Based on a generalization of field and laboratory engineering-geological data, sections and a map of the engineering-geological zoning of the city of Olmaliq were compiled.